Case Report: Intramedullary Intervertebral Disk Extrusion in a Cat: Clinical, Computed Tomographic, High-Field Magnetic Resonance Imaging, and Outcome Findings - Debreuque, Maud; Valin, Isabelle; Prata, Daniela; De Fornel, Pauline; Thibaud, Jean-Laurent (Frontiers in Veterinary Science, 2020)
Background: Intramedullary disk extrusions has rarely been described in veterinary medicine, more especially in cats, with only two cases are reported in the veterinary literature. Diagnosis may be difficult, even though clinical presentation and imaging studies, such as MRI or CT, can present specific features. Treatment and prognosis are not clearly described. Case presentation: A 10-year-old domestic shorthair female cat was evaluated for a 12 h-history of peracute-onset of paraparesis with flaccid tail and urinary and fecal incontinence. The patellar reflexes were normal, the pelvic flexor reflexes were decreased (more markedly on the right limb) and the perianal reflex was absent. The tail was flaccid, without nociception. Abdominal palpation revealed a small urinary bladder, easily expressed. Manipulation of the lumbar vertebral column elicited marked pain. Neurological examination was consistent with a L7-caudal segments lesion. A lumbosacral MRI and CT evaluations were performed and revealed a focal intramedullary hemorrhagic lesion, with an associated vertical linear tract communicating with the L5-L6 intervertebral disk space, and a suspected intramedullary focus of mineralization. These imaging findings were highly suggestive of an L5-L6 intramedullary disk extrusion. A dorsal L5-L6 laminectomy confirmed the presence of intramedullary degenerative nucleus pulposus fragments, which were surgically removed. Rapid and progressive neurological improvement was observed post-surgery. At the 1-year follow-up, right plantigrade stance and mild paraparesis were still noticed, but jumps and voluntary tail movements were observed. Occasional urinary and fecal incontinence episodes remained. Conclusions: This is the first feline case report of an intramedullary disk herniation with long-term follow-up available. Clinical description, CT and High-Field MRI findings, surgical procedure and histological results are reported, and help describing the characteristics of this rare non-compressive category of peracute intervertebral disk extrusion. Surgical management may be considered in feline cases of intramedullary disk herniation and may be associated with a good outcome.